Gulf war lessons for third world countries: a case study of Indonesia and Malaysia - Hossain, Ishtiaq (The Centre for Public Affairs, University of Dhaka, Bangladesh, 1993)
This paper aims to review and analyze the reactions of Indonesia and Malaysia to the political-military course and outcome of the Gulf war. The paper addresses three general areas of inquiry: i) objective analysis by the two countries of the course and outcome of the conflict; ii) political-miiitary lessons learned by them; and iii) the assessment by those countries of the United States. While these are not exhaustive, the areas identified here should provide a useful framework for assessing the two countries' response to the Gulf crisis. The paper first analyzes Indonesia's response to the crisis followed by that of Malaysia. assessing the two countries' response to the Gulf crisis. The paper fiist analyzes defend the Kingocr- : lndonesia's response to the crisis followed by that of Malaysia